Negotiating the sacred : blasphemy and sacrilege in a multicultural society - Coleman, Elizabeth Burns, 1961-; White, Kevin (ANU E Press, 2006)
"This cross-disciplinary exploration of the role of the sacred, blasphemy and sacrilege in a multicultural society brings together philosophers, theologians, lawyers, historians, curators, anthropologists and sociologists, as well as Christian, Jewish and Islamic and secular perspectives. In bringing together different disciplinary and cultural approaches, the book provides a way of broadening our conceptions of what might count as sacred, sacrilegious and blasphemous, in moral and political terms. In addition, it provides original research data on blasphemy, sacrilege and religious tolerance from a range of disciplines."--Publisher's description